Argentina : Second Review Under the Stand-By Arrangement and Request for Augmentation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The review focuses on fiscal consolidation and on structural reforms to improve productivity and competitiveness in the economy. The continuing recession hindered the implementation of the fiscal program for 2000. The authorities fully recognize the importance of reassuring domestic and foreign investors about their commitment to medium-term fiscal attainability. The authorities have responded to the adverse developments by strengthening the growth orientation of their economic program, through measures aimed at promoting a recovery of investment and an accelerated implementation of structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet